Demystifying Neonatal Thrombocytopenia: An In-Dependent Exploration of Etiological Roots - Noman , Obaid (Journal of Biomedical and Pharmaceutical Research, 2018)
Introduction: Neonatal thrombocytopenia, characterised by a low platelet count during the early stages of life, presents a significant clinical challenge with potential risks for affected infants. This original article aims to shed light on the etiology of thrombocytopenia in neonates through a comprehensive study. By investigating the underlying factors that contribute to this condition, we seek to improve our understanding of its origins and provide valuable information for enhanced management strategies. The implications of this research extend beyond understanding etiology; they hold promise for effectively managing neonatal thrombocytopenia. By identifying specific risk factors and their interplay, healthcare practitioners can tailor diagnostic approaches and treatment strategies to optimize patient outcomes. Additionally, this study paves the way for future investigations aimed at targeted interventions and preventive measures.Methods: A prospective, cross-sectional, single center study was carried out on 180 NICU patients having thrombocytopenia in a tertiary care rural hospital over a period of 2 yearsName, sex, gestational age, age at thrombocytopenia onset, and birth weight were among the demographic information that was noted. The enrolled newborns' parents or guardians were contacted to get information, and specifics regarding their clinical and demographic characteristics were recorded. The structured questionnaire that interviewers used to gather data was pretested and adjusted before being employed in the study. Based on research conducted in laboratories, data was gatheredData was collected in structured forms and a master sheet was made on Microsoft excel. The data that was evaluated was presented as percentages and figures.Results: A total of 180 cases of neonates admitted in NICU having thrombocytopenia were studied a male preponderance was observed with 66% (99) males and 44% (81) females. Moderate degree 40% (72 cases) of thrombocytopenia was most commonly encountered followed by mild 35%(63 cases) and then severe  degree 25% (45 cases). Highest number of below normal gestational age (below 37 weeks) neonates was observed followed by term neonates(37-42weeks), no neonate having above than normal (more than 42 weeks) gestational age was seen in our studyA number of etiological factors with lots of overlapping leading to thrombocytopenia was seen in neonates sepsis being the most common and consistent aetiology followed by less age of gestation at birth, Meconium aspiration syndrome, birth asphyxia, respiratory distress syndrome, DIC, Jaundice, Intra uterine growth retardation Sepsis was found to be the most common cause of severe thrombocytopenia followed by prematurity the distribution of etiology as per severity of thrombocytopenia as per aetiology can be been in the table below.Conclusion: This original article offers a comprehensive examination of the etiology of thrombocytopenia in neonates. By unraveling the intricacies of this condition, we provide valuable insights that contribute to our understanding of the underlying factors involved. Ultimately, this knowledge has the potential to enhance clinical decision-making, improve patient care, and lay the foundation for further advancements in the field of neonatal thrombocytopenia.Keywords: DIC, Jaundice, Neonatal thrombocytopenia